Miscarriage Australia: the use of a human centered design approach to design and develop a website for those affected by miscarriage - Bilardi, Jade; Webb, Amy; Trieu, Van-Hau; Sharp, Gemma; McIntosh, Jennifer; Temple-Smith, Meredith (Frontiers in Public Health, 2023)
Background Past research has shown that Australians affected by miscarriage want a website specific to both miscarriage and their local region that is accessible, comprehensive, evidence-based and informed by experts. The aim of this study was to design, develop and evaluate the Miscarriage Australia website using human centered design. Methods A four stage human centered design approach was used to develop the Miscarriage Australia website which aimed to: (1) Understand the issue and why users need a website; (2) Define users’ specific needs; (3) Design solutions to meet those needs; and (4) Evaluate the design by testing with end users. Across the four stages, various types of data and data analysis were developed and utilized including interviews, desktop research, development of personas and tone of voice, followed by usability testing. Process and content were guided by designers, developers and an expert advisory committee of key stakeholders. Results Analysis and synthesis of user research across Stages 1 and Stage 2 found 11 key themes pertaining to user’s miscarriage experiences and support needs. Using the themes, common experiences, goals, motivations and behaviors of users were identified and similar user types grouped and used to inform the development of two personas. Using the personas and user research findings, design elements (Stage 3) including the “tone of voice guidelines” were developed recommending the Miscarriage Australia website be calm, empathetic, hopeful and authoritative. The tone of voice guidelines guided branding and over 100 pages of content was informed by the research team and reviewed by a 13-member Expert Clinical Advisory Committee over two rounds to ensure it was evidence based and reflected best practice. Using a contextual inquiry approach, usability testing was undertaken with 8 end users to test a low fidelity mockup and high-fidelity prototype of the website. Overall, end users reported the website was highly acceptable in terms of the design, content, layout, language and terminology, describing it in line with the intended tone of voice. Users reported the website was easy to use and navigate and provided useful and appropriate content and resources. Minor areas for improvement included slight changes to specific images, improved links for navigating sections, and a title change to one section heading. Conclusion The Miscarriage Australia website was successfully implemented and commended by users as meeting their needs. As a result of using human centered design, the Miscarriage Australia website provides an ideal template or blueprint on how to develop a successful and useful digital resource for users, particularly around sensitive women’s health issues.